Decrease in the Particle Size and Coercivity of Self‐Assembled CoNi Nanoparticles Synthesized Under a Repulsive Magnetic Field. (10th April 2019) - ur Rehman, Sajid; Ahmed, Rida; Liu, Jian; Wang, Jingmin; Sun, Mingze; Fang, Zhenbin; Aslam, Muhammad Adnan; Morais, Paulo Cesar; Wang, Chunchang; Bi, Hong
Abstract: Towards the challenge for synthesis of smaller‐sized heterostructures and hybrid composites for nanomagnets and magnetic fluid applications. Here, a novel method is reported to reduce the particle size of Cobalt–Nickel (CoNi) magnetic nanoparticles by placing them between a static, repulsive magnetic field (N–N/S–S) during synthesis in contrast to the conventional method of applying an attractive (N–S) magnetic field. The obtained smaller sized‐CoNi nanoparticles (≈40 nm) possess a uniform size, an excellent monodispersity, and outstanding magnetic properties. The results clearly demonstrate that the size and morphology change of CoNi nanoparticles have great influence on their magnetic properties. This study provides a footprint to design new heterostructured magnetic nanomaterials under the same‐poled magnetic field for potential applications in magnetic fluids, spintronics, and other related industries. Abstract : A novel synthesis method is used to reduce the particle size of CoNi magnetic nanoparticles under a repulsive magnetic field. It is shown that by reducing the particle size, the value of coercivity decreases and saturation magnetization gradually increases.